Refractive indices vs deposition temperature of thin films of ethanol, methane and nitrous oxide in the vicinity of their phase transition temperatures - Drobyshev, A.; Aldiyarov, A.; Sokolov, D.; Shinbayeva, A.; Tokmoldin, N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
This paper presents results of an experimental study of the dependence of deposition temperature on the refractive in dices of ethanol, methane and nitrous oxide, in the form of cryovacuum deposited thin films, in the vicinity of their structural transformation temperatures. The measurements were made using a two-beam laser interferometer in the temperature range 14–130 K. The refractive indices of ethanol, methane and nitrous oxide demonstrate clear non-monotonic dependence on deposition temperature in the vicinity of their structural phase transformation temperatures. It is speculated that the observed abrupt changes in the refractive indices are due to a difference in the number of translational and rotational degrees of freedom of the molecules existing in different phase states of these cryocrystals.